Astrocytes Downregulate Inflammation in Lipopolysaccharide-Induced Acute Respiratory Distress Syndrome: Applicability to COVID-19 - Izrael, Michal; Molakandov, Kfir; Revel, Ariel; Slutsky, Shalom Guy; Sonnenfeld, Tehila; Weiss, Julia Miriam; Revel, Michel (Frontiers in Medicine, 2021)
Background: Acute respiratory distress syndrome (ARDS) is caused by increased amounts of pro-inflammatory cytokines and neutrophil-mediated tissue injury. To date, there is no effective treatment for ARDS, while the need for one is growing due to most severe complications of the current COVID-19 pandemic. Human astrocytes have shown immunomodulatory properties in the central nervous system. The aim of this study was therefore to evaluate the capacity of astrocytes to decrease lung inflammation and to be applied as treatment therapy in ARDS. Methods: First, we assessed the ability of clinical grade human astrocytes (AstroRx) to suppress T-cell proliferation in a mixed lymphocyte reaction test. Next, we tested the therapeutically potential of AstroRx cells in an LPS-based ARDS mouse model by injecting AstroRx intravenously. We determined the degree of lung injury by using a severity scoring scale of 0-2, based on the American Thoracic Society. The scoring measured the presence of neutrophils, fibrin deposit and the thickening of alveolar walls. The state of inflammation was further assessed by quantifying immune-cell infiltration to the bronchoalveolar lavage fluid (BALF) and by the presence of proinflammatory cytokines and chemokines in bronchoalveolar lavage fluid and serum. Results: We detected that AstroRx cells were capable to suppress T-cell proliferation in-vitro after exposure to the mitogen Concanavalin A. In vivo, AstroRx cells were able to lower the degree of lung injury in LPS-treated animals compared to sham injected animals. 30% of AstroRx treated mice showed no lung lesions (responder mice), these mice presented a steady number of macrophages, DCs, T cells and neutrophils comparable to the level of naïve control mice. Inflammatory cytokines and chemokines such as TNFα, IL1b, IL-6 and CXCL1 were also kept in check in responder AstroRx-treated mice and were not upregulated as in sham-injected mice. As a result, LPS-treated ARDS mice had a higher survival rate when they were treated with AstroRx. Conclusions: Our results demonstrate the immunosuppressive activity of AstroRx cells support the application of AstroRx cells as a cell-therapy treatment for ARDS. The immunoregulatory activity may also be part of the mechanism of action of AstroRx reported in ALS neurodegenerative disease.